Thienopyrimidinedione Formation Versus Ester Hydrolysis from Ureido Carboxylic Acid Methyl Ester - Reille-Seroussi, Marie; Labruère, Raphaël; Inguimbert, Nicolas; Broussy, Sylvain; Gagey-Eilstein, Nathalie; Liu, Wang-Qing; Vidal, Michel; Huguenot, Florent (Synthesis, 2013)
The basic hydrolysis of ureidothienyl carboxylic esters was found to depend on the substitution pattern of the ureido moiety. While various hindered substituents led to carboxylic acid formation, unhindered substituents preferentially resulted in a cyclization step, yielding thienopyrimidinedione derivatives.
Keywords: carboxylic acids; esters; hydrolysis; heterocycles; steric hindrance